Harnessing olaparib, palbociclib, and endocrine therapy: A phase I/II trial of olaparib, palbociclib and fulvestrant in patients with BRCA mutation-associated, hormone receptor-positive, human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (HOPE) - Aaron, Megan; White, Lia; D'Andrea, Kurt; Narayan, Vivek; Knollman, Hayley Michelle; Bradbury, Angela R.; Tung, Nadine M.; Robson, Mark E.; Nathanson, Katherine; Domchek, Susan M.; Shah, Payal Deepak (Journal of clinical oncology, 2023)
TPS1126Background: Hormone receptor-positive (HR+) metastatic breast cancer (MBC) in patients (pts) with germline or somatic BRCA1 or BRCA2 (g/sBRCA1/2) mutations has dual drivers: hormone receptor signaling and homologous recombination deficiency. The PALOMA-3 trial showed superiority of fulvestrant (F) with palbociclib (P) compared to F alone. The OlympiAD trial showed the poly-ADP ribose polymerase inhibitor (PARPi) olaparib (O) to be superior to chemotherapy in BRCA1/2-associated MBC. However, treatment resistance inevitably develops; targeting dual therapeutic drivers concurrently may delay or circumvent resistance. O and P have overlapping hematologic toxicity and the safety of combined O, P and F is unknown. The tolerability of O + P is particularly relevant given the emergence of potentially less myelosuppressive PARPi. Methods: HOPE (NCT03685331) is a phase I/II trial to evaluate safety and efficacy of O, P and F in pts with g/sBRCA1/2-associated, HR+ MBC. Eligible pts have an ECOG performance status 0-1, measurable/evaluable breast cancer, any/no prior endocrine therapy, and 0-2 lines of chemotherapy for MBC. Prior platinum is allowed for curative intent if completed at least 12 months prior to MBC diagnosis, or for MBC if no progression during therapy. Prior PARPi and CDK4/6i are permitted on phase I, and are permitted during phase II if there was no progression on them. Treatment (28-day cycles) consists of: O orally twice daily continuously; F 500mg intramuscularly on day 1 of each cycle plus load; and P orally once daily on days 1-21. Phase I begins with a 28-day safety run-in of O and F alone. O and P doses are based on dose level (DL): DL 0 (starting level), O 300mg, P 75mg; DL 1, O 300mg, P 100mg; DL 2, O 300mg, P 125mg; DL-1, O 250mg, P 75mg and DL-2, O 200mg, P 75mg. For phase II, O and P will be dosed at MTD. Pts have tissue collection at baseline and peripheral blood cfDNA analysis at baseline, at progression, and at all scan timepoints (every 3 cycles). Phase I primary endpoint is MTD. A 3+3 dose escalation design is used with a 30% rate of dose limiting toxicity (DLT) deemed acceptable, and 6 patients treated at a dose for it to be declared MTD. A minimum of 2 and a maximum of 18 patients will be enrolled on the phase I. Phase II primary endpoint is PFS using Kaplan-Meier methods and secondary efficacy endpoints are objective response rate and 24-week clinical benefit rate. Phase II will evaluate 54 subjects to provide 80% power to detect an increase in PFS from 7 months with O monotherapy to 10 months. Exploratory objectives include examination of baseline tissue for PARPi predictive biomarkers and measures of tumor immunogenicity as well as serial serum evaluation for reversion mutations. Enrollment is ongoing. Clinical trial information: NCT03685331.